If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3)(x + 2) = 0 Reorder the terms: (3 + x)(x + 2) = 0 Reorder the terms: (3 + x)(2 + x) = 0 Multiply (3 + x) * (2 + x) (3(2 + x) + x(2 + x)) = 0 ((2 * 3 + x * 3) + x(2 + x)) = 0 ((6 + 3x) + x(2 + x)) = 0 (6 + 3x + (2 * x + x * x)) = 0 (6 + 3x + (2x + x2)) = 0 Combine like terms: 3x + 2x = 5x (6 + 5x + x2) = 0 Solving 6 + 5x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (3 + x)(2 + x) = 0Subproblem 1
Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3Subproblem 2
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Solution
x = {-3, -2}
| 3x-3=3x-6 | | 2x+x-4=2x-4-2 | | 2x+x-4=2x-6 | | x*3.2+0.8=x*5.7-0.4 | | 3x-4=2x-6-2 | | x^2-5x+11=0 | | x^2+16x-5=0 | | -16x^2+64x+50=0 | | Y=35-5x | | 2(-x)-(-3+x)=2x+8 | | 1.25x+2.45=0.3 | | 9x-7(x-1)= | | 3x^2+12x+14=0 | | 15x^2-12x=0 | | (9a^3+3a^2)+(5a^3+6a^2)= | | x^2+9x-13=0 | | (-3x)(2)=x+2+3x | | 5a+2c=3280 | | 10x-1=x | | 13-7x=2x+58 | | x=0.5 | | 5z-7=13-3z | | s(s-6)=-8 | | 16x=(30x-15)-20 | | 6n^2+2n-140=0 | | b^2+6b-7=0 | | 4c^2+9xy-9y^2= | | -3v+10=40 | | 7p^2-4p=0 | | 16x^2-96x-100=0 | | 3k^2-22k+24=0 | | 2b+9=25 |